Lessons learned from setting up a hospital-based national registry for venous thromboembolic disorders in India - Sumit Aggarwal; Peteneinuo Rulu; Heena Tabassum (Journal of Family Medicine and Primary Care)
Introduction: Health registries are instrumental in tracking trends in the number of people with diseases, monitoring treatment options, and assessing health outcomes. This research examines the challenges of establishing and maintaining a venous thromboembolism (VTE) registry in the Indian context. Methods: A mixed-method approach with purposive sampling was conducted to capture the challenges faced by individuals playing key roles in the establishment and operation of the national registry on VTE. This study focused on 10 questions related to technological infrastructure, resource optimization, data collection and management, coordination and collaboration, regulatory compliance, and political influences and were documented using a semi-structured questionnaire and telephonic interviews. Results: Technological, recruitment, and follow-up challenges were prominently highlighted with issues related to data entry, system glitches, changes to the data entry forms, and potential participant reluctance. Conclusion: Findings from this study highlight the multifaceted challenges experienced during the establishment of a national registry on VTE. By integrating insights from our findings into suggestions, this discussion reflects the specific challenges faced by the research project and offers evidence-based strategies for mitigating these challenges.